Cable Based and Wireless Charging Systems for Electric Vehicles : Technology and Control, Management and Grid Integration. - Singh, Rajiv (Institution of Engineering & Technology, 2022)
Electric Vehicles are part of the solution to both reducing urban air pollution and staving off climate change. This book covers the latest in charging technology, both stationary as well as wireless and in-motion. Grid integration, simulations, fast charging, and battery management are also addressed.
Keywords: Electric batteries.; Electric cables.; Electric power transmission.; Electric vehicles.; Energy conservation.; Hybrid electric vehicles.; Power electronics.; elektronické knihy; electronic books